Application of the Problem-Based Learning Model to Improve the Learning Outcomes of Islamic Education Students at SMK 2 Sibolga - Ajisman; Tanjung, Eryanto; Caniago, Rinaldi (Jurnal Pendidikan Profesi Guru, 2023)
This research aims to improve student learning outcomes in Islamic religious education learning by using problem based learning. This research is classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research were vocational high school students. This research data was obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with indicators of research success. The research results show that problem based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of pre-cycle 40.19%, first cycle 66.87% and in the second cycle it increased to 82.32%. Thus, the use of problem based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.